Policy of Sustainable Development State Regulation of Mongolian Industry - S. Amarsanaa; N. G. Alent’eva; E. L. Plisetskii; Yu. N. Shed’ko (Управленческие науки, 2020)
The paper presents the results of the analysis of state policy realization regarding sustainable development of industry in Mongolia. The study gives the reason for recovery of macroeconomics stability (in the short term) and transfer to a more stable and diversified economy model (in the longer term) as well as on the basis of the Russian experience necessity of using modern forms of regional industry organization. Consequently, it is explained the essentiality of structural changes, development of financial intermediation, investment in infrastructure and regional integration with the purpose of increase the level of regions interconnection and access to foreign markets. The purpose of the research is to define priority activities of the economic growth as well as measures focused on improvement of state management concerning sustainable industry development in Mongolia. To this effect there are used monographic and economic statistic research methods. It is concluded that relating to definite countries and regions taking into account the peculiarities it is advisable to explore the system of indexes, capable of measuring the results (and estimating efficiency) of sustainable development of economics industries. Thus, economic growth in Mongolia is possible only as a subject to partnership relations with the countries that have innovation technologies, know-how and attracting finance from foreign investors. Thereupon sustainable development of Mongolian industry, including mining industry depends on such factor as a possibility of application of the high technology in traditional economic activity, digital transformation of the industry, increase of human capital, environmental conditions. There are defined the conditions of realization of sustainable development strategy of Mongolian industry, for example forming territorial innovation industrial clusters and assuring effective cooperation between government, business and society at the regional level. There are proposed the measures regarding improvement of institutional environment of Mongolian industry. There are specified the tasks necessary to be solved for the purpose of setting the regions of industrial development and complex industrial planning.